Beyond the pandemic: Lessons for the future of SOTL in the global South (part two) - Michael Samuel; Shireen Motala; Zach Simpson (University of Johannesburg, 2022)
The third biennial SOTL in the South Conference took place online between November 22 and 25, 2021. The theme of the conference was 'Beyond the Pandemic: Lessons for the Future of SOTL in the Global South'. This theme was in response to the COVID-19 pandemic, which raised fundamental and urgent questions for the scholarship of teaching and learning. Emerging from the conference were a number of papers that sought to address questions regarding the challenges associated with academic life in lockdown and the transition to online teaching and learning. These papers examined these questions from a diversity of perspectives: student, lecturers, support staff, and academic managers. A first collection of these papers was released in April 2022. This collection privileged the perspectives of university management, lecturers, academic advisors, doctoral supervisors and tutors. In this, the second part of our collection of papers emerging from the 2021 SOTL in the South conference, greater focus is placed on student perspectives in response to the COVID-19 pandemic.